Aligned Arrays of Na2Ti3O7 Nanobelts and Nanowires on Carbon Nanofiber as High‐Rate and Long‐Cycling Anodes for Sodium‐Ion Hybrid Capacitors. Issue 2 (23rd November 2020) - Wang, Huanwen; Xu, Dongming; Qiu, Ruyun; Tang, Shasha; Li, Shuai; Wang, Rui; He, Beibei; Gong, Yansheng; Fan, Hong Jin
Abstract : Sodium‐ion capacitors (SICs) have attracted extensive attentions due to their integration of high‐energy battery and high‐power capacitor as well as the naturally abundant sodium resource. A major challenge of current SICs is to achieve high rate performance and long‐cycle stability of the battery‐type anode. Herein, fast sodium storage is achieved from sodium titanate (Na2 Ti3 O7 ) arrays that are uniformly grown on highly conductive carbon nanofiber networks with a high mass loading of 5.6 mg cm −2 . Nanowires and nanobelts of Na2 Ti3 O7 are both synthesized, and their Na‐ion storage properties are compared. Both arrays can be used as binder‐free and flexible electrodes, but the nanobelts exhibit higher specific capacity and better rate performance than the nanowires with similar mass loading. The difference between two types of nanostructures is ascribed to their different kinetics in ion/charge transport, according to the electrochemical impedance data. SIC full devices consisting of the Na2 Ti3 O7 nanobelt anode and biomass‐derived porous carbon cathode are constructed, which show pretty high specific energy and power performance. Abstract : Both Na2 Ti3 O7 nanobelt and nanowire arrays with high mass loadings (5.6 mg cm −2 ) are grown on carbon nanofiber networks, and their performance in Na‐ion storage is compared systematically. The full Na‐ion capacitor device demonstrates high power performance and ultrastability.